The New Regulation of the Minister of Finance on Financial Instruments - an Overview of Selected Changes - Biśta, Anna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
The review article is dedicated to the issues of financial instruments in the context of the new regulation of the Minister of Finance on the recognition and valuation methods, as well as the disclosure and presentation of financial instruments. This regulation came into effect on 13 December 2024, replacing the previous regulation from the year 2001, and applies for the first time to financial statements prepared for the year 2025, with the possibility of earlier application. The article reviews and analyses the changes introduced by the new regulation in selected areas, i.e., the scope of the new regulation, basic definitions (excluding derivatives and hedge accounting), classification, and reclassification of financial instruments. The research methods employed in this study include critical and comparative analyses of legal acts. The discussion shows that although the analysed changes are not revolutionary, it is worth examining them more closely as they eliminate many doubts that may have arisen during the application of the previous regulation, for example, in the classification and reclassification of financial instruments. The changes introduced also harmonise the new regulation of financial instruments with other regulations, e.g., the Accounting Act.